Ethics as a minor form of politics and theory in activist research (Diametros, 2024)
To do minor activist research is to create and make use of critical neologistic vocabularies hopefully balancing the ascetic impoverishment of direction and syntax in majority vocabularies when conceptualized as universals. To do minor activist research is therefore to unsettle received discourses, narratives, and material social practices of power to develop means of resistance in new and different registers. To do minor activist research is to train the imagination for a collaboratively accomplished re/presentation of data through creating points of encounters, thus engendering an affirmative perspectivist’s ethos. Re/presenting data as a space in which one’s own thinking is challenged, hence providing a perspective of the storying practices across participants and across different disciplinary, ideological, or personal boundaries within the researcher’s and the researched specific positioning. This requires getting everyone to participate in the “analysis” of data, and then getting everyone “inside” the text: situating data-inquiries in immanence. It therefore demands a liberation from old scripts, and challenges how everyone is transformed into text, with perspectivism being simultaneously means and objective for avoiding the reproduction of both old scripts and ethics. Our goal is to enhance (self)reflexivity regarding knowledge production and research methodologies, to influence actual research practices through fostering a more inclusive, open, and collaborative approach to research that transcends traditional boundaries and embraces the fluid and hybrid nature of knowledge production. Ultimately, turning the concept of ethics through minoring into a thinking hub and pedagogy for change.The first and theoretical section is on how to ethically represent data in a new-empiricist and post qualitative environment. We call it data-philosophy. Our ontological approach brings its own concepts, which reflect the perspectives from which we argue. In the three next sections, we follow up by looking more closely into these ideas in re/presenting empirical qualitative research to invite hybrid and fluid configurations. Here, activist research refers to bringing actors into our thinking about the data, to accentuate the collaborative, open to thinking differently through staying close to the data. We then bring it all together in a section on the rebirth of language, to open for what we refer to as a storying personifying, thereby storying data together as a process of becoming, of mutuality and affect as a source of agency. We argue that this creates a theory of science and ethics in data analysis, and in re/presenting data, which are closely entangled.